2021
DOI: 10.1007/s11033-021-06535-2
|View full text |Cite
|
Sign up to set email alerts
|

Neuroregulatory role of ginkgolides

Abstract: The application of ginkgolides as a herbal remedy reaches ancient China. Over time many studies confirmed the neuroprotective effect of standard Ginkgo biloba tree extract—the only available ginkgolide source. Ginkgolides present a wide variety of neuroregulatory properties, commonly used in the therapy process of common diseases, such as Alzheimer’s, Parkinson’s, and many other CNS-related diseases and disorders. The neuroregulative properties of ginkgolides include the conditioning of neurotransmitters actio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 47 publications
0
7
0
1
Order By: Relevance
“…Amongst these, we also identified Ginkgolide as a potential biomolecules with neuroprotective action (Table 2). Ginkgolide is known to increase neuronal cell viability by suppressing the NF-κB pathway in cells mimicking AD disease [13]. Incidentally, VFE was found to be enrich in carotenes family (12%-15%) after GC-MS analysis (Table 2).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Amongst these, we also identified Ginkgolide as a potential biomolecules with neuroprotective action (Table 2). Ginkgolide is known to increase neuronal cell viability by suppressing the NF-κB pathway in cells mimicking AD disease [13]. Incidentally, VFE was found to be enrich in carotenes family (12%-15%) after GC-MS analysis (Table 2).…”
Section: Discussionmentioning
confidence: 98%
“…They possess anti-inflammatory, anti-coagulant, antioxidant, anti-apoptotic, and immunomodulatory properties, contributing to neuroprotection. Similarly, carotenoids, prevalent lipid-soluble pigments in plants, microalgae, and more, play a crucial role in neuroprotection alongside their varied therapeutic effects like anticancer, anti-inflammatory, and immunomodulatory functions [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Entre os flavonoides encontrados no extrato Research, Society and Development, v. 11, n. 12, e88111233441, 2022 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v11i12.33441 GB2 utilizado neste estudo, estão kaempferol, quercetina e isoquercetina. Os gincoflavonoides e as terpenolactonas são reconhecidos como os marcadores de qualidade dos extratos (Amin et al, 2012;Gachowska et al, 2021). Os flavonoides são substâncias fenólicas estáveis por ressonância e possuem grande número de grupos funcionais hidroxila redutores nos flavonoides, que podem prevenir e inibir a toxicidade dos radicais livres de oxigênio, reduzindo os danos da peroxidação de lipídios e outros danos patológicos ao corpo humano (Zhang et al, 2021).…”
Section: Avaliação Fitoquímicaunclassified
“…Based on the differences in molecular structure of the active ingredients, there are several different ginkgolides in GB (4). Evidence showed that biflavonoids and ginkgolides have many biological activities such as antiinflammatory, anti-allergic, antioxidant, anti-cancer, and neuroprotective activities (2,5). The extracts from GB have been converted to drugs, such as ginkgo lactone injection, ginkgolide injection, and ginkgo leaf dropping pills (4).…”
Section: Study Protocolmentioning
confidence: 99%